2020
DOI: 10.1111/opn.12334
|View full text |Cite
|
Sign up to set email alerts
|

Staff nurses' evaluation of care process quality and patient outcomes in long‐term care hospitals: A cross‐sectional questionnaire survey

Abstract: Aim: Despite the large and growing body of research on quality care evaluation and improvements in long-term care facilities, issues regarding the quality of care provided prevail worldwide. Further and more diverse research related to this topic is urgently required. To that end, this study examines the association between the subjective care process evaluations of nurses and selected patient outcomes in Japanese long-term care hospitals. Method: To conduct a cross-sectional survey, we approached 2,000 long-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Our separate analysis using the same data set also found a significant association between nurses’ perceived quality of care and select patient outcomes (Yamamoto‐Mitani et al., 2020). Thus, it is important to be sensitive to what the nurses regarded as professional work.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Our separate analysis using the same data set also found a significant association between nurses’ perceived quality of care and select patient outcomes (Yamamoto‐Mitani et al., 2020). Thus, it is important to be sensitive to what the nurses regarded as professional work.…”
Section: Discussionmentioning
confidence: 66%
“…Nurses’ perception of the care process was assessed using an 18‐item instrument with three subcategories: care process quality, staff support and teamwork. This instrument was specifically developed for this study, and its content and construct validity, and internal consistency were confirmed, although a full psychometric evaluation was not conducted (Yamamoto‐Mitani et al., 2020). Their reasons for choosing the current workplace were elicited through a list of eight possible motives, such as interest in elderly care, many educational opportunities, commuting convenience or employment stability, and they had to respond by choosing ‘yes’ or ‘no’ for each reason.…”
Section: Methodsmentioning
confidence: 94%
“…The principal research question was "Is objectively measured care quality in LTC wards related to staff nurses' burnout?" Data reported in this manuscript are a part of a broader research project [23][24][25]. The current topic and results are distinct with no redundancy or duplication between the current study and any of the published studies from the same research project.…”
Section: Introductionmentioning
confidence: 95%